Efficiency exceeding 10% for inverted polymer solar cells with a ZnO/ionic liquid combined cathode interfacial layer1. Issue 20 (28th May 2015) - Yu, W.; Huang, L.; Yang, D.; Fu, P.; Zhou, L.; Zhang, J.; Li, C.
<x xml:space="preserve">Abstract</x> With the ZnO/IL interfacial layer, PTB7-Th : PC71BM i-PSCs can exhibit a champion PCE of 10.15%.